Huntington's Disease - Molecular Pathogenesis and Current Models 2017
DOI: 10.5772/66438
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Modifiers of CAG.CTG Repeat Instability in Huntington's Disease Mouse Models

Abstract: Huntington's disease (HD) is a dominantly inherited neurodegenerative disorder whose characterstics were first described by George Huntington in 1872. Several decades later, in 1993, the mutation behind this disease was found to be an unstable expanded CAG repeat within exon 1 of the HTT gene localized on the short arm of chromosome 4. The majority of HD patients carry more than 40 CAG repeats, which become unstable and usually increase in size in successive generations and in tissues. In order to dissect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…In aging, larger numbers of reactive astrocytes (A1) are observed in CA1 and striatal regions that, in turn, induce neuroinflammation and vulnerability in pyramidal neurons and MSNs of CA1 and striatal regions, respectively (Clarke et al, 2018). Studies have shown age-dependent increase in the β-amyloid, α-synuclein, SOD1, and Htt protein aggregation (Kennedy, 2000;Ishiguro et al, 2001;Lee et al, 2011;Tomé and Dandelot, 2017;Medinas et al, 2018Medinas et al, , 2019. Because of the energy crisis, this type of aggregation leads to enormous stress in the specific neuronal classes.…”
Section: Role Of Agingmentioning
confidence: 99%
“…In aging, larger numbers of reactive astrocytes (A1) are observed in CA1 and striatal regions that, in turn, induce neuroinflammation and vulnerability in pyramidal neurons and MSNs of CA1 and striatal regions, respectively (Clarke et al, 2018). Studies have shown age-dependent increase in the β-amyloid, α-synuclein, SOD1, and Htt protein aggregation (Kennedy, 2000;Ishiguro et al, 2001;Lee et al, 2011;Tomé and Dandelot, 2017;Medinas et al, 2018Medinas et al, , 2019. Because of the energy crisis, this type of aggregation leads to enormous stress in the specific neuronal classes.…”
Section: Role Of Agingmentioning
confidence: 99%